Modal Adverbs Used as Hedges in Research Articles - Martirosyan, Naira; Ghazaryan, Tatev (Armenian Folia Anglistika, 2013)
The major aim of the author of a scientific text is to introduce his/her opinion as convincingly as possible trying to make an impact on the reader. Since it is not possible to ensure a direct connection between the reader and the author in written speech, it is necessary to create a field of a dialogue where certain words denoting conviction, uncertainty, indecisiveness and approximation are often used to qualify the information. In this regard, modal words are of special interest.